Penerapan Metode SAW Sistem Pendukung Keputusan Bantuan Pupuk RDKK pada Petani Wilayah Hutan: (Studi Kasus Hutan Kayen) - Yanwar Adi Nurcahyo; Muhammad Imam Ghozali; Wibowo Harry Sugiharto (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2024)
Fertilizer is one component that is really needed by farmers, to maintain soil fertility and increase production results from their agriculture. So, it is not surprising that the need for fertilizer for farmers in Indonesia is very high. The government continues to encourage efficient use of fertilizer through appropriate pricing policies, procurement and distribution, so the role of fertilizer is very important for farmers. The author created a Decision Support System which aims to assist in determining recipients of subsidized fertilizer assistance appropriately and on target. The author uses the Simple Additive Weighting (SAW) method in creating a decision support system, where in the decision making process, determines the weighting value for each alternative attribute, followed by a matrix normalization process which is compared with the best alternative ranking process. The results of the research carried out are a system that can help and make it easier to determine the priorities of farmers in the Kayen forest area who are entitled to receive RDKK subsidized fertilizer, with the right target in terms of selecting from the ranking results of the best alternatives.